A comprehensive review on the state-of-the-art of piezoelectric energy harvesting - Nurettin Sezer (14778217) (2021)
The global energy crisis and environmental pollutions caused mainly by the increased consumption of nonrenewable energy sources prompted researchers to explore alternative energy technologies that can harvest energies available in the ambient environment. Mechanical energy is the most ubiquitous ambient energy that can be captured and converted into useful electric power. Piezoelectric transduction is the prominent mechanical energy harvesting mechanism owing to its high electromechanical coupling factor and piezoelectric coefficient compared to electrostatic, electromagnetic, and triboelectric transductions. Thus, piezoelectric energy harvesting has received the utmost interest by the scientific community. Advancements of micro and nanoscale materials and manufacturing processes have enabled the fabrication of piezoelectric generators with favorable features such as enhanced electromechanical coupling factor, piezoelectric coefficient, flexibility, stretch-ability, and integrate-ability for diverse applications. Besides that, miniature devices with lesser power demand are realized in the market with technological developments in the electronics industry. Thus, it is anticipated that in near future, many electronics will be powered by piezoelectric generators. This paper presents a comprehensive review on the state-of-the-art of piezoelectric energy harvesting. The piezoelectric energy conversion principles are delineated, and the working mechanisms and operational modes of piezoelectric generators are elucidated. Recent researches on the developments of inorganic, organic, composite, and bio-inspired natural piezoelectric materials are reviewed. The applications of piezoelectric energy harvesting at nano, micro, and mesoscale in diverse fields including transportation, structures, aerial applications, in water applications, smart systems, microfluidics, biomedicals, wearable and implantable electronics, and tissue regeneration are reviewed. The advancements, limitations, and potential improvements of the materials and applications of the piezoelectric energy harvesting technology are discussed. Briefly, this review presents the broad spectrum of piezoelectric materials for clean power supply to wireless electronics in diverse fields. Other Information Published in: Nano Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nanoen.2020.105567